Doxazosin Treatment Attenuates Carbon Tetrachloride-Induced Liver Fibrosis in Hamsters through a Decrease in Transforming Growth Factor β Secretion (Gut and Liver, 2016)
Background/AimsThe development of therapeutic strategies for the treatment of cirrhosis has become an important focus for basic and clinical researchers. Adrenergic receptor antagonists have been evaluated as antifibrotic drugs in rodent models of carbon tetrachloride (CCl4)-induced cirrhosis. The aim of the present study was to evaluate the effects of carvedilol and doxazosin on fibrosis/cirrhosis in a hamster animal model.Methods : Cirrhotic-induced hamsters were treated by daily administration of carvedilol and doxazosin for 6 weeks. Hepatic function and histological evaluation were conducted by measuring biochemical markers, including total bilirubin, aspartate aminotransferase, alanine aminotransferase and albumin, and liver tissue slices. Additionally, transforming growth factor β (TGF-β) immunohistochemistry was analyzed.Results : Biochemical markers revealed that hepatic function was restored after treatment with doxazosin and carvedilol. Histological evaluation showed a decrease in collagen type I deposits and TGF-β-secreting cells.Conclusion : sTaken together, these results suggest that the decrease in collagen type I following treatment with doxazosin or carvedilol is achieved by decreasing the profibrotic activities of TGF-β via the blockage of α1- and β-adrenergic receptor. Consequently, a diminution of fibrotic tissue in the CCl4-induced model of cirrhosis is achieved.